Analisis Beban Kerja Fisik Dan Mental Terhadap Rider Grab Menggunakan Metode Cardiovascular Load (CVL) Dan Subjective Workload Assesment Technique (SWAT) (Studi Kasus: Rider Grab Domisili Kelurahan Balas Klumprik Kecamatan Wiyung) - Muhammad Zaky Mubarok; Rusindiyanto Rusindiyanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Online motorcycle taxis are a mode of transportation that is widely used today. Online motorbike taxis are very quickly accepted by the public because of the ease of ordering and are application-based which can be easily downloaded by smartphone users on both Android and iOS systems. Thanks to online motorcycle taxis, passengers no longer need to wait on the side of the road to be picked up. In addition, passengers do not have to participate in negotiations, because the price has been determined per kilometer by the application system. The presence of online motorcycle taxis also adds jobs for the people of Indonesia.